ISLAMIC ACCOUNTING AS A SOLUTION TO ANTHROPOCENTRISM IN COASTAL ENVIRONMENTAL AND ECONOMIC MANAGEMENT - Aptasari, Fety Widianti Aptasari; Falah, Muhammad Helmi; Adha, Rishan; Jumaedi, Jumaedi (Ekonomi Islam, 2025)
Research aims: This study aims to analyze the application of Islamic-based accounting principles as an alternative approach to anthropocentrism in managing the environment and coastal economic systems. Design/Methodology/Approach: This research employs a qualitative approach through case studies in several Indonesian coastal communities. Data were collected through in-depth interviews, observations, and document analysis, and then interpreted to identify Islamic values relevant to sustainable accounting practices. Research findings: The findings reveal that the application of Islamic principles such as amanah (responsibility), mizan (balance), and the prohibition of israf (excessiveness) can shift the paradigm of resource management from short-term profit orientation toward ecological and social sustainability. This approach has the potential to reduce coastal environmental degradation and enhance the welfare of local communities. Theoretical Contribution/Originality: This study proposes a conceptual framework of Islamic-based accounting as an alternative to the conventional accounting model that tends to be anthropocentric, thereby expanding the discourse on sustainability accounting from an Islamic value-based perspective. Practitioners/Policy Implications: The findings may serve as a foundation for policymakers and practitioners in designing fair and sustainable accounting policies for coastal environmental and economic management based on Islamic ethical principles. Research Limitations/Implications: This study is limited to the local context of Indonesian coastal areas; further research is needed to examine the applicability of the proposed model in different social and economic settings.